Investigating the effect of nitrate on juvenile turbot (Scophthalmus maximus) growth performance, health status, and endocrine function in marine recirculation aquaculture systems - Jiachen Yu; Yanfeng Wang; Yongshuang Xiao; Xian Li; Li Zhou; Yunong Wang; Tengfei Du; Xiaona Ma; Jun Li (Ecotoxicology and Environmental Safety, 2021)
Nitrate (NO3−), a potential toxic nitrogenous compound to aquatic animals, is distributed in aquatic ecosystems worldwide. The aim of this study was to investigate the effects of different NO3− levels on growth performance, health status, and endocrine function of juvenile turbot (Scophthalmus maximus) in recirculating aquaculture systems (RAS). Fish were exposed to 0 mg/L (control, CK), 50 mg/L (low nitrate, LN), 200 mg/L (medium nitrate, MN), and 400 mg/L (high nitrate, HN) NO3-N for 60 d in experimental RAS. Cumulative survival (CS) was significantly decreased with increasing NO3− levels in LN, MN, and HN. The lowest CS was 35% in the HN group. Growth parameters, including absolute growth rate, specific growth rate, and feed conversion rate, were significantly different in HN compared with that in the CK. Histological survey of gills and liver revealed dose-dependent histopathological damage induced by NO3− exposure and significant differences in glutamate pyruvate transaminase and glutamate oxalate transaminase in MN and HN compared with that in the CK. The hepatosomatic index in HN was significantly higher than that in the CK. Additionally, NO3− significantly increased bioaccumulation in plasma in LN, MN, and HN compared to that in the CK. Significant decreases in hemoglobin and increases in methemoglobin levels indicated reduced oxygen-carrying capacity in HN. Additionally, qRT-PCR and enzyme-linked immunosorbent assay (ELISA) were developed to investigate key biomarkers involved in the GH/IGF-1, HPT, and HPI axes. Compared with that in the CK, the abundance of GH, GHRb, and IGF-1 was significantly lower in HN, whereas GHRa did not differ between treatments. The plasma T3 level significantly decreased in LN, MN, and HN and T4 significantly decreased in HN. The CRH, ACTH, and plasma cortisol levels were significantly upregulated in HN compared with that in the CK. We conclude that elevated NO3− exposure leads to growth retardation, impaired health status, and endocrine disorders in turbot and the NO3− level ...